Temperature dependent electron transport behavior of poly (methyl methacrylate)/silver functionalized reduced graphene oxide films - Asha, S. (AIP Conference Proceedings, 2018)
Poly (methyl methacrylate) (PMMA) and silver functionalized reduced graphene oxide film were prepared and were investigated using FTIR and Raman. Electron transport behavior of these samples, at low temperature were studied. The prepared film exhibited a temperature dependent electron transport, at higher temperatures Arrhenius-like temperature dependence of resistance was observed indicating band like electron transport with a small thermal activation energy. At further lower temperatures hopping mechanism of conduction was observed due to the presence of defects. The conduction due to band-like electron transport at higher temperature is attributed to the easier excitation of charge carriers to the conduction band, whereas at lower temperatures conduction occurs through hopping mechanism due to localized states around Fermi level in the presence of defects.